Preparation method of pre-filled needle with rapid and long-term anti-inflammatory, analgesic and tissue repair promoting effects

By using a sustained-release material of small and medium molecular weight aminoglycan and tanshinone IIA sulfonic acid, combined with hydroxypropyl cellulose and crosslinked sodium hyaluronate, to form a sustained-release preparation, the long-term problems of adverse reactions after injection cosmetics are solved. It achieves rapid and long-term anti-inflammatory, analgesic and tissue repair effects, and improves the stability and safety of the drug.

CN119185650APending Publication Date: 2024-12-27DONGFANG YANMEI (CHENGDU) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333763.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Patients often experience long-term adverse reactions after injecting cosmetic products, such as redness, edema, lumps, itching, local and systemic inflammation. The existing anti-inflammatory and analgesic drugs have rapid efficacy but are short-lasting, making it difficult to meet the long-term treatment needs.

Method used

Use a salt or composite formed by moderate small and medium molecular weight aminoglycans and prototype tanshinone IIA sulfonic acid as a sustained release material, combining medium viscosity hydroxypropyl cellulose and higher molecular weight crosslinked sodium hyaluronate to form sustained release Preparation, combined with tanshinone sodium sulfonate, to achieve rapid and long-term anti-inflammatory, analgesic and promote tissue repair.

Benefits of technology

It achieves rapid and long-term anti-inflammatory, analgesic and promotes tissue repair effects, has good stability, is salt-tolerant and high ionic strength, reduces the incidence of side effects, and extends the drug's sustained release time.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a pre-filling needle, which comprises the following steps: dispersing prototype amino glycan with small molecular weight, prototype amino glycan with medium molecular weight and hydroxy propyl cellulose with medium viscosity into water, and adding a hydrochloric acid solution; adding prototype tanshinone IIA sulfonic acid nano-scale powder or a water dispersion liquid thereof; adding a hot water solution of tanshinone IIA sodium sulfonate; cross-linked sodium hyaluronate is added; and adding the polycaprolactone microspheres and / or the polymethyl methacrylate microspheres and / or the polylactic acid copolymer and / or the glycerol, adding water to the total amount, and uniformly mixing to obtain the composite material. The pre-filling needle has the effects of quickly resisting inflammation, easing pain and promoting tissue repair for a long time; the stability is good, and salt resistance and high ion strength resistance are realized; 'dumping 'is avoided; the occurrence rate of side effects is lower, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A method for preparing a prefilled needle. Specifically, it relates to a method for preparing a prefilled needle having rapid and long-term anti-inflammatory, analgesic and tissue repair promoting effects. Technical Background

[0002] Injectable beauty is a cosmetic procedure that uses specific fillers to improve facial contours, fill in facial depressions and fine lines. This technique uses a fine needle to inject specific ingredients into specific areas to achieve the purpose of lifting contours, increasing volume and improving wrinkles. Injectable beauty can achieve a more natural effect, and the filler can be customized according to the individual's facial features and needs.

[0003] However, after the injection of beauty products, local reactions such as redness, swelling, edema, lumps, itching, and discomfort may occur at the implantation site; some irritants may prolong the duration of these adverse reactions, such as excessive exposure to sunlight, overheating, drinking, improper use of cosmetics and skin care products, etc. A small number of patients may have local allergic reactions to this product, resulting in redness, swelling, nodules, urticaria, etc., most of which can be relieved within a month; some patients may cause inflammation, cyst formation, suppuration reaction, and in severe cases, scar tissue may form, and wound infection may also occur.

[0004] After the injection of injectable beauty products, patients may also experience systemic adverse reactions, including: cold-like symptoms (such as fever, headache, neuralgia, muscle pain, nausea, physical discomfort, dizziness), itching, skin rash, tingling, numbness, temporary blurred vision, temporary multi-joint pain and systemic immune diseases.

[0005] If patients experience the above-mentioned adverse reactions after injecting cosmetic products, they need appropriate drug treatment.

[0006] The above-mentioned adverse reactions of injectable beauty products last for a long time.

[0007] Therefore, in reality, it is necessary to prepare a prefilled injection preparation that has obvious anti-inflammatory, analgesic and tissue repair promoting effects with rapid efficacy and long duration. Summary of the invention

[0008] Salvia miltiorrhiza is a perennial plant belonging to the Lamiaceae family, Salvia genus, and is a shade herb. The dried roots and rhizomes of Salvia miltiorrhiza are commonly known as Danshen in China. As a widely used traditional Chinese medicine, it has a long history of nearly 2,000 years and has the effects of promoting blood circulation and removing blood stasis, relieving pain through menstruation, clearing the heart and eliminating vexation, cooling blood and eliminating carbuncle. The active ingredients of Salvia miltiorrhiza are complex and have multiple pharmacological effects. The plant and its extracts have pharmacological effects such as anti-inflammatory, antioxidant, anti-atherosclerotic, anti-tumor, anti-fibrosis, and protection against diabetic nephropathy.

[0009] One of its extracts, Tanshinone ⅡA, has the following pharmacological activities: natural antioxidant effect, cardiovascular pharmacological effect, anti-infection effect, protection of nerve cells, sex hormone-like activity, protection of liver, kidney and lung, enhancement of body immune function, analgesia, anti-aging and other effects.

[0010] It has been confirmed that sodium tanshinone ⅡA sulfonate has anti-inflammatory, analgesic, platelet aggregation inhibition, anti-oxidation, tissue repair promotion, bacterial growth inhibition and other effects and functions. Sodium tanshinone ⅡA sulfonate has the effect of inhibiting the release of inflammatory mediators and the expression of cytokines, thereby alleviating symptoms such as tissue redness and swelling. The drug relieves the transmission of pain signals by blocking the nerve conduction pathway and has a certain analgesic effect. Sodium tanshinone ⅡA sulfonate has the ability to scavenge free radicals, which helps protect cells from oxidative stress damage. The drug can interfere with the adhesion and aggregation between platelets, prevent thrombosis, and promote tissue repair.

[0011] Therefore, tanshinone ⅡA sulfonic acid can achieve the purpose of the present invention.

[0012] However, the duration of the efficacy of tanshinone ⅡA sulfonic acid is short, and tanshinone ⅡA sulfonic acid needs to be made into a sustained-release preparation. The salt (or complex) formed by using moderate small and medium molecular weight amino polysaccharides and prototype tanshinone ⅡA sulfonic acid can form a sustained-release material.

[0013] The present invention has been achieved based on the above-mentioned facts.

[0014] The present invention relates to a method for preparing a prefilled needle having rapid and long-term anti-inflammatory, analgesic and tissue repair promoting effects (clinical efficacy), the method comprising:

[0015] 1) Disperse the prototype amino polysaccharide with a molecular weight of 1000-5000 Dalton, the prototype amino polysaccharide with a molecular weight of 10000-50000 Dalton, and the hydroxypropyl cellulose with a molecular weight of 100,000-400,000 Dalton in water, wherein the concentration of the prototype amino polysaccharide with a molecular weight of 1000-5000 Dalton is 3-5% wt / wt (based on the final total amount of 100%, that is, 3-5 parts per 100 parts by weight), and the prototype amino polysaccharide with a molecular weight of 10000-50000 Dalton is 3-5% wt / wt (based on the final total amount of 100%, that is, 3-5 parts per 100 parts by weight). -50000 Dalton prototype amino polysaccharide has a concentration of 1-3% wt / wt (based on 100% of the final total amount, i.e., 1-3 parts per 100 parts by weight), and the above hydroxypropyl cellulose has a concentration of 2-6% wt / wt (based on 100% of the final total amount, i.e., 2-6 parts per 100 parts by weight), and hydrochloric acid solution is added, wherein the (molar) amount of hydrochloric acid is 0.4-0.7 times the (molar) amount of the total amino groups in the above amino polysaccharide, and mixed to obtain liquid A;

[0016] 2) Add the prototype tanshinone ⅡA sulfonic acid nanopowder or its aqueous dispersion to liquid A, wherein the molar amount of tanshinone ⅡA sulfonic acid is 0.3-0.6 times the total molar amount of amino groups in the above amino polysaccharide, mix well, and place at room temperature for 12-24 hours to obtain liquid B;

[0017] 3) Add a hot aqueous solution of sodium tanshinone ⅡA sulfonate to liquid B, wherein the molar amount of sodium tanshinone ⅡA sulfonate is 0.1-0.3 times the molar amount of the above-mentioned prototype tanshinone ⅡA sulfonic acid, and mix well to obtain liquid C;

[0018] 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 1-5% wt / wt (based on the final total amount of 100%, i.e., 1-5 parts per 100 parts by weight) to obtain liquid D;

[0019] 5) Add polycaprolactone microspheres and / or polymethyl methacrylate microspheres and / or polylactic acid copolymer and / or glycerol to liquid D, add water to the total amount, mix well, and obtain the product. DETAILED DESCRIPTION

[0020] The concentration of the hydroxypropyl cellulose is preferably 3-4% wt / wt.

[0021] The concentration of the cross-linked sodium hyaluronate is preferably 2-4% wt / wt.

[0022] The hydroxypropyl cellulose is selected from Klucel JF (having a molecular weight of about 140,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt) and / or Klucel GF (having a molecular weight of about 370,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 2% wt / wt).

[0023] The present invention uses salts (or complexes) formed by moderately small and medium molecular weight amino polysaccharides and prototype tanshinone ⅡA sulfonic acid as the main sustained-release material and the main sustained-release mechanism. They can release tanshinone ⅡA sulfonic acid at two moderately different speeds, providing sustained-release effects at medium speeds and lower speeds, thereby achieving a longer-term anti-inflammatory, analgesic and tissue repair-promoting effect.

[0024] In the present invention, the salt (or complex) formed by the lower or higher viscosity molecular weight amino polysaccharide and the prototype tanshinone ⅡA sulfonic acid releases tanshinone ⅡA sulfonic acid too slowly (no or weak anti-inflammatory, analgesic and tissue repair promoting effects) or too quickly (significant side effects), and fails to meet the requirements of the present invention.

[0025] The invention is simultaneously formulated with an appropriate amount of sodium tanshinone ⅡA sulfonate to release tanshinone ⅡA sulfonic acid at a conventional speed, thereby achieving the effects of anti-inflammatory, analgesic and promoting tissue repair at a relatively fast speed.

[0026] The invention adds hydrochloric acid solution to convert part of the amine groups in the prototype amino polysaccharide into amine ions to form acidic amino polysaccharide, which can enhance its solubility, prevent its precipitation and aggregation, and increase viscosity and enhance sustained release effect. In addition, it is also beneficial to prevent the aggregation and precipitation of the salt (or complex) formed by the amino polysaccharide and the prototype tanshinone ⅡA sulfonic acid.

[0027] The present invention also uses medium viscosity hydroxypropyl cellulose and relatively high molecular weight cross-linked sodium hyaluronate as auxiliary sustained-release materials. The medium viscosity hydroxypropyl cellulose and relatively high molecular weight cross-linked sodium hyaluronate are used to enhance the sustained-release effect and prolong the sustained-release time, thereby further prolonging the anti-inflammatory, analgesic and tissue repair promoting action time.

[0028] The functions of medium-viscosity hydroxypropyl cellulose also include: 1) preventing the aggregation and precipitation of salts (or complexes) formed by amino polysaccharides and prototype tanshinone ⅡA sulfonic acid, especially in the presence of salt, especially in the state of high ionic strength;

[0029] 2) It can also prevent the aggregation and precipitation of high molecular weight cross-linked sodium hyaluronate in the presence of salt, especially in high ionic strength conditions, especially in the presence of calcium salt and magnesium salt.

[0030] In the present invention, the hydroxypropyl cellulose with a lower viscosity has a poor blocking effect and is difficult to prevent aggregation and precipitation due to its low viscosity, and the above-mentioned effect cannot be achieved. The hydroxypropyl cellulose with a higher viscosity has a high viscosity and is not used in large amounts, and has a poor salt resistance effect and is also difficult to prevent aggregation and precipitation, and the above-mentioned effect cannot be achieved; in addition, due to its high viscosity, the operation is difficult or the process becomes complicated, for example, the above-mentioned room temperature placement time (i.e., the formation time of the salt (or complex) formed by the amino polysaccharide and the prototype tanshinone Ⅱ A sulfonic acid) is too long.

[0031] Medium-viscosity hydroxypropyl cellulose cannot achieve the above-mentioned effects, which will affect the sustained-release effect, resulting in no or weak anti-inflammatory, analgesic and tissue repair effects, or short-duration anti-inflammatory, analgesic and tissue repair effects, making it difficult to achieve a longer-term anti-inflammatory, analgesic and tissue repair effect, and even causing "dumping" of tanshinone ⅡA sulfonic acid, that is, a one-time rapid release, which may result in serious side effects.

[0032] The advantages of the present invention over the prior art are:

[0033] 1) It can not only fight inflammation, relieve pain and promote tissue repair at a relatively fast speed, but also fight inflammation, relieve pain and promote tissue repair for a relatively long time;

[0034] 2) Good stability, resistance to salt and high ionic strength;

[0035] 3) Not “pouring out”;

[0036] 4) Lower incidence of side effects.

[0037] Example

[0038] The following non-optional example, i.e., the method for preparing a prefilled needle, further describes a preferred embodiment within the scope of the present invention. There are many variations of these embodiments within the scope of the present invention.

[0039] Example 1

[0040] 1) Mix the prototype amino polysaccharide with a molecular weight of 1000-5000, the prototype amino polysaccharide with a molecular weight of 10000-50000, and the medium viscosity hydroxypropyl cellulose Klucel JF (whose molecular weight is about 140,000 Daltons and viscosity is 150-400 mPa·s at a concentration of 5% wt / wt) is dispersed in water, wherein the concentration of the prototype amino polysaccharide with a molecular weight of 1000-5000 is 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight), the concentration of the prototype amino polysaccharide with a molecular weight of 10000-50000 is 3% wt / wt (based on 100% of the final total amount, i.e., 3 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight), and a hydrochloric acid solution is added, wherein the (molar) amount of hydrochloric acid is 0.55 times the (molar) amount of the total amino groups in the above amino polysaccharide, to obtain liquid A;

[0041] 2) Add the prototype tanshinone ⅡA sulfonic acid nanopowder or its aqueous dispersion to liquid A, wherein the molar amount of tanshinone ⅡA sulfonic acid is 0.45 times the total molar amount of the amino groups in the amino polysaccharide, mix well, and place at room temperature for 12-24 hours to obtain liquid B;

[0042] 3) Add a hot aqueous solution of sodium tanshinone ⅡA sulfonate to liquid B, wherein the molar amount of sodium tanshinone ⅡA sulfonate is 0.25 times the molar amount of the above-mentioned prototype tanshinone ⅡA sulfonic acid, and mix well to obtain liquid C;

[0043] 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain liquid D;

[0044] 5) Add 6% wt / wt (based on the final total amount of 100%, that is, 6 parts per 100 parts by weight) of polycaprolactone microspheres and 10% wt / wt (based on the final total amount of 100%, that is, 10 parts per 100 parts by weight) of glycerol to liquid D, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).

[0045] Comparative Example 1-1

[0046] The prototype amino polysaccharide with a molecular weight of 1000-5000 in Example 1 was replaced with a prototype amino polysaccharide with a molecular weight of 100-500, and the rest remained unchanged.

[0047] Comparative Example 1-2

[0048] The prototype amino polysaccharide with a molecular weight of 10,000-50,000 in Example 1 was replaced with a prototype amino polysaccharide with a molecular weight of 100,000-250,000, and the rest remained unchanged.

[0049] Example 2

[0050] 1) Disperse the prototype amino polysaccharide with a molecular weight of 1000-5000, the prototype amino polysaccharide with a molecular weight of 10000-50000, and the medium viscosity hydroxypropyl cellulose Klucel JF in water, wherein the concentration of the prototype amino polysaccharide with a molecular weight of 1000-5000 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), the concentration of the prototype amino polysaccharide with a molecular weight of 10000-50000 is 2% wt / wt (based on the final total amount of 100%, that is, 2 parts per 100 weight parts in the end), and the concentration of hydroxypropyl cellulose is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), add hydrochloric acid solution, wherein the (molar) amount of hydrochloric acid is 0.5 times the (molar) amount of the total amino groups in the above amino polysaccharide, to obtain liquid A;

[0051] 2) Add the prototype tanshinone ⅡA sulfonic acid nanopowder or its aqueous dispersion to liquid A, wherein the molar amount of tanshinone ⅡA sulfonic acid is 0.5 times the total molar amount of the amino groups in the amino polysaccharide, mix well, and place at room temperature for 12-24 hours to obtain liquid B;

[0052] 3) Add a hot aqueous solution of sodium tanshinone ⅡA sulfonate to liquid B, wherein the molar amount of sodium tanshinone ⅡA sulfonate is 0.3 times the molar amount of the above-mentioned prototype tanshinone ⅡA sulfonic acid, and mix well to obtain liquid C;

[0053] 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 4% wt / wt (based on the final total amount of 100%, i.e., 4 parts per 100 parts by weight) to obtain colloidal solution D;

[0054] 5) Add 5% wt / wt (based on the final total amount of 100%, i.e., 5 parts per 100 parts by weight) of PMMA microspheres and 12% wt / wt (based on the final total amount of 100%, i.e., 12 parts per 100 parts by weight) of glycerol to liquid D, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).

[0055] Comparative Example 2-1

[0056] 90% of the amount of the prototype amino polysaccharide with a molecular weight of 1000-5000 in Example 2 (ie, 10% of the original amount) is replaced with the prototype amino polysaccharide with a molecular weight of 10000-50000, and the rest remains unchanged.

[0057] Comparative Example 2-2

[0058] 90% of the amount of the prototype amino polysaccharide with a molecular weight of 10000-50000 in Example 2 (ie, 10% of the original amount) was replaced with the prototype amino polysaccharide with a molecular weight of 1000-5000, and the rest remained unchanged.

[0059] Example 3

[0060] 1) Disperse the prototype amino polysaccharide with a molecular weight of 1000-5000, the prototype amino polysaccharide with a molecular weight of 10000-50000, and the medium-viscosity hydroxypropyl cellulose Klucel GF in water, wherein the concentration of the prototype amino polysaccharide with a molecular weight of 1000-5000 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), the concentration of the prototype amino polysaccharide with a molecular weight of 10000-50000 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 weight parts in the end), and the concentration of hydroxypropyl cellulose is 4% wt / wt (based on the final total amount of 100%, that is, 4 parts per 100 weight parts in the end), add hydrochloric acid solution, wherein the (molar) amount of hydrochloric acid is 0.5 times the (molar) amount of the total amino groups in the above amino polysaccharide, to obtain liquid A;

[0061] 2) Add the prototype tanshinone ⅡA sulfonic acid nanopowder or its aqueous dispersion to liquid A, wherein the molar amount of tanshinone ⅡA sulfonic acid is 0.5 times the total molar amount of the amino groups in the amino polysaccharide, mix well, and place at room temperature for 12-24 hours to obtain liquid B;

[0062] 3) Add a hot aqueous solution of sodium tanshinone ⅡA sulfonate to liquid B, wherein the molar amount of sodium tanshinone ⅡA sulfonate is 0.1 times the molar amount of the above-mentioned prototype tanshinone ⅡA sulfonic acid, and mix well to obtain liquid C;

[0063] 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain liquid D;

[0064] 5) Add 5% wt / wt (based on the final total amount of 100%, i.e., 5 parts per 100 parts by weight) of polylactic acid copolymer microspheres and 8% wt / wt (based on the final total amount of 100%, i.e., 8 parts per 100 parts by weight) of glycerol to liquid D, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).

[0065] Comparative Example 3-1

[0066] The concentration of hydroxypropyl cellulose in Example 3 was changed from 4% wt / wt to 0.4% wt / wt, and the other contents remained unchanged.

[0067] Comparative Example 3-2

[0068] The concentration of hydroxypropyl cellulose in Example 3 was changed from 4% wt / wt to 12% wt / wt, and the other contents remained unchanged.

[0069] The method of the above prototype amino polysaccharide is as follows:

[0070] Dissolve the commercially available chitosan with a molecular weight of 100,000-500,000 Daltons and a deacetylation degree of not less than 95% in a three-necked flask with 2-5% acetic acid, heat in a water bath to 60-70°C, add H2O2 at a uniform rate while stirring to a concentration of 3-6%, keep warm for 4-6 hours, then add 5% sodium hydroxide solution to the reaction solution, adjust the pH to 4-6, and successively use pore sizes of 250,000 Daltons, 100,000 Daltons, 50,000 Daltons, 100,000 Daltons, 5000 Daltons, 100,000 Daltons, 150, ... The mixture was filtered through nanofiltration membranes with molecular weights of 100,000-250,000 Daltons, 10,000-50,000 Daltons, 1000-5000 Daltons, respectively; the mixture was then neutralized to neutrality (pH = 7), and acetone with a volume twice that of the reactant was added dropwise under stirring. The mixture was allowed to stand overnight, and the degradation product was filtered out by suction, washed with acetone, and dried under reduced pressure.

[0071] Test Example 1

[0072] The samples of the embodiment and the control example were made into prefilled needles and sterilized by γ-ray irradiation.

[0073] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests and intradermal injection experiments have demonstrated that the prefilled needle is non-toxic, has no hemolytic effect, is non-irritating, does not contain pyrogenic substances, has stable performance and good biocompatibility.

[0074] 4968 patients with moderate to severe nasolabial wrinkles were subcutaneously injected with 2 mL of the above prefilled needle on both sides of their faces, and the tissue repair promoting effect (clinical efficacy) of the prefilled needles containing the embodiment and the control example was compared and observed. The anti-inflammatory and analgesic effects of the prefilled needles containing the embodiment and the control example were compared and observed.

[0075] Effectiveness evaluation

[0076] (1) Effectiveness of wrinkle correction (evaluation of the effect of promoting tissue repair): The researchers used the 5-level grading method of WSRS to grade: Grade 1 (absent), no obvious nasolabial folds, continuous skin line; Grade 2 (mild), shallow and visible nasolabial folds with slight creases, mild facial features; Grade 3 (moderate), deep nasolabial folds, clear facial features can be seen in normal appearance, but not visible when stretched; Grade 4 (severe), very long and deep nasolabial folds, prominent facial features, visible wrinkles <2 mm when stretched; Grade 5 (extremely severe), extremely deep and long nasolabial folds, not conducive to facial appearance, and V-shaped wrinkles of 2-4 mm can be seen when stretched.

[0077] (2) Analgesic effect evaluation: The visual analogue scale (VAS) of pain in the embodiment and control groups was calculated at rest and in motion 1 day, 2 days and 3 days after surgery, respectively. The score of no pain was 0, the score of disturbing sleep was 5, and the score of severe pain was 10. The higher the score, the more severe the pain.

[0078] (3) Evaluation of anti-inflammatory effect: Record the adverse events of inflammation such as tissue redness and swelling that occurred in the subjects during the entire clinical trial. Inflammation incidence rate = number of subjects with inflammation / number of subjects × 100%.

[0079] Data processing

[0080] SPSS 23.0 software was used for statistical analysis. Count data were expressed as percentages, and the comparison of observation indicators at different times after treatment was performed using the χ2 test. Measurement data were expressed as mean ± standard deviation, and the comparison before and after treatment and at different times after treatment was performed using the t test. P < 0.05 indicated that the difference was statistically significant.

[0081] The results of the effective rate of nasolabial fold wrinkle correction of the subjects who received the sample treatment 1 month, 2 months and 3 months after the treatment are shown in Table 1.

[0082] The VAS score results of the subjects after receiving the sample treatment are shown in Table 2.

[0083] Table 3 Inflammation incidence rate of subjects before and 2, 4, and 7 days after treatment with samples

[0084] Table 1-1 Effectiveness of nasolabial wrinkle correction in Example 1 and its control example 1 month, 2 months and 3 months after treatment (%)

[0085] January February March Example 1 53.7 82.8 93.3 Comparative Example 1-1 26.7 41.7 53.2 Comparative Example 1-2 62.8 66.8 71.5

[0086] Table 1-2 Effectiveness of nasolabial wrinkle correction in Example 2 and its control example 1 month, 2 months and 3 months after treatment (%)

[0087] January February March Example 2 52.7 86.4 95.6 Comparative Example 2-1 60.8 68.6 77.5 Comparative Example 2-2 30.5 45.8 60.8

[0088] Table 1-3 Effectiveness of nasolabial wrinkle correction in Example 3 and its control example 1 month, 2 months and 3 months after treatment (%)

[0089] January February March Example 3 44.8 75.8 90.3 Comparative Example 3-1 50.3 66.6 70.7 Comparative Example 3-2 -★ - -

[0090] ★ Note: No sample was obtained and turbidity was not tested. In control example 3-2, the viscosity of hydroxypropylcellulose Klucel GF was too high, resulting in a jelly-like sample, which made uniform mixing and other operations difficult. The prototype tanshinone ⅡA sulfonic acid was dispersed in a particle state and the sample was turbid, while the example sample was a clear (colloidal) solution.

[0091] The results show that compared with the control example, the embodiment has better drug release performance and better therapeutic effect. The control example releases the drug too fast or too slow: if the drug is released too fast, there is no drug to be released in the middle and late stages, and the drug concentration in the middle and late stages is seriously low, which makes the efficacy in the middle and late stages low, while the drug concentration in the early stage is high, and the efficacy in the early stage is slightly increased, but the side effects may increase more; if the drug is released too slowly, the effective drug concentration cannot be increased, which seriously affects the efficacy and makes the overall efficacy low.

[0092] Table 2-1 VAS score results after the subjects received sample treatment

[0093] 1 day 2 days 3 days Example 1 2.64±0.43 3.08±0.57 3.67±0.62 Comparative Example 1-1 3.77±0.65 4.68±0.67 5.42±0.75 Comparative Example 1-2 2.25±0.48 2.85±0.49 3.37±0.63

[0094] Table 2-2 Results of VAS scores after subjects received sample treatment

[0095] 1 day 2 days 3 days Example 2 2.52±0.45 3.02±0.53 3.42±0.60 Comparative Example 2-1 2.13±0.41 2.65±0.45 3.31±0.56 Comparative Example 2-2 3.63±0.65 4.51±0.67 5.25±0.78

[0096] The results show that the embodiments have substantially equivalent or better analgesic properties than the control examples.

[0097] Compared with the embodiment, the control example releases the drug too quickly or too slowly: if the drug is released too quickly, the analgesic effect is better initially and then tends to be consistent; if the drug is released too slowly, the effective drug concentration cannot be increased and the overall analgesic effect is low.

[0098] Table 3-1 Inflammation incidence results of subjects 2 days, 4 days and 7 days after treatment

[0099] 2 days 4 days 7 days Example 1 12‰ 8‰ 4‰ Comparative Example 1-1 25‰ 17‰ 12‰ Comparative Example 1-2 10‰ 8‰ 6‰

[0100] Table 3-2 Inflammation incidence results of subjects 2 days, 4 days and 7 days after treatment

[0101] 2 days 4 days 7 days Example 2 14‰ 9‰ 5‰ Comparative Example 2-1 12‰ 10‰ 8‰ Comparative Example 2-2 30‰ 23‰ 18‰

[0102] The results show that the embodiments have substantially equivalent or better anti-inflammatory properties than the control examples.

[0103] Compared with the embodiment, the control example releases the drug too quickly or too slowly: if the drug is released too quickly, the anti-inflammatory effect is slightly better initially, and then tends to be the same or worse; if the drug is released too slowly, the effective drug concentration cannot be increased, and the overall anti-inflammatory effect is low.

[0104] Test Example 2

[0105] The samples of the embodiment and the control example were diluted with physiological saline (added with 0.05% calcium ion) at a ratio of 1:1 and placed at room temperature for 0, 1, 2, 4 and 6 months, and the turbidity values ​​(NTU) were measured using a Hach turbidimeter.

[0106] The results are shown in Table 4.

[0107] Table 4 Turbidity values ​​(NTU) measured in Example 3 and its comparative example

[0108] 0 month January February April June Example 3 2.3 2.7 3.3 4.2 5.6 Comparative Example 3-1 4.7 6.9 11.3 18.6 32.5 Comparative Example 3-2 -★ - - - -

[0109] ★ Note: No sample was obtained and turbidity was not tested. In control example 3-2, the viscosity of hydroxypropylcellulose Klucel GF was too high, resulting in a jelly-like sample, which made uniform mixing and other operations difficult. The prototype tanshinone ⅡA sulfonic acid was dispersed in a particle state and the sample was turbid, while the example sample was a clear (colloidal) solution.

[0110] The results show that the embodiments have lower turbidity values, better dispersion, smaller particles, better storage stability, and higher salt resistance than the control examples.

Claims

1. A method for preparing a prefilled needle having rapid and long-term anti-inflammatory, analgesic and tissue repair promoting effects, the method comprising: 1) Disperse the prototype amino polysaccharide with a molecular weight of 1000-5000 Dalton, the prototype amino polysaccharide with a molecular weight of 10000-50000 Dalton, and the hydroxypropyl cellulose with a molecular weight of 100,000-400,000 Dalton in water, wherein the concentration of the prototype amino polysaccharide with a molecular weight of 1000-5000 Dalton is 3-5% wt / wt, i.e., 3-5 parts are contained in every 100 parts by weight, the concentration of the prototype amino polysaccharide with a molecular weight of 10000-50000 Dalton is 1-3% wt / wt, i.e., 1-3 parts are contained in every 100 parts by weight, and the concentration of the hydroxypropyl cellulose is 2-6% wt / wt, i.e., 2-6 parts are contained in every 100 parts by weight, add hydrochloric acid solution, wherein the molar amount of hydrochloric acid is 0.4-0.7 times the total molar amount of amino groups in the amino polysaccharide, mix well, and obtain liquid A; 2) Add the prototype tanshinone ⅡA sulfonic acid nanopowder or its aqueous dispersion to liquid A, wherein the molar amount of tanshinone ⅡA sulfonic acid is 0.3-0.6 times the total molar amount of the amino groups in the above amino polysaccharide, mix well, and place at room temperature for 12-24 hours to obtain liquid B; 3) Add a hot aqueous solution of sodium tanshinone ⅡA sulfonate to liquid B, wherein the molar amount of sodium tanshinone ⅡA sulfonate is 0.1-0.3 times the molar amount of the above-mentioned prototype tanshinone ⅡA sulfonic acid, and mix well to obtain liquid C; 4) Add cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to liquid C at a concentration of 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight, to obtain liquid D; 5) Add polycaprolactone microspheres and / or polymethyl methacrylate microspheres and / or polylactic acid copolymer and / or glycerol to liquid D, add water to the total amount, mix well, and obtain the product.

2. The preparation method according to claim 1, characterized in that The concentration of the hydroxypropyl cellulose is 3-4% wt / wt.

3. The preparation method according to claim 1, characterized in that The concentration of the cross-linked sodium hyaluronate is 2-4% wt / wt.

4. The preparation method according to claim 1, characterized in that The hydroxypropyl cellulose is selected from hydroxypropyl cellulose having a molecular weight of about 140,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt and / or hydroxypropyl cellulose having a molecular weight of about 370,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 2% wt / wt.

5. The preparation method according to claim 1, characterized in that The hydroxypropyl cellulose is selected from Klucel JF and / or Klucel GF.